Interaksi Di Kawasan Mangrove Balang Baru Dalam Menunjang Pembelajaran Ekosistem Kelas X SMA - Sartinayanti Sartinayanti (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
The learning process requires interaction, both interaction between students and teachers and interaction between students and their environment. Interactions in an ecosystem are two interrelated components, namely biotic and abiotic components. The mangrove forest ecosystem as a biological natural resource has a diversity of potential that provides benefits to human life. The research formulation is How Interaction in the Balang Baru Mangrove Area Supports Ecosystem Learning for Class X SMA Students. The aim of the research is to determine interactions in the Balang Baru Mangrove Area in Supporting Ecosystem Learning for Class X SMA Students. It is hoped that the benefits of research through this research can provide benefits for students, schools and the government in terms of learning. Consumers are living creatures that utilize organic materials from producers to ensure their survival because they cannot make their own food, where consumers consist of herbivores as primary consumers (I) and carnivores who eat herbivores as secondary consumers (II). The types of interactions in the Mangrove Area of ​​Balang Baru Village are mutualism, competition and commensalism symbiosis.